'Farmer behaviour may affect the actual contribution of badger perturbation to bTB'. (13th November 2020) - Enticott, Gareth
Abstract : Gareth Enticott argues that precise assessment of the effect of badger perturbation to bTB incidence can only be made by analysing farmer behaviour and its effects in badger culling zones.